2017
DOI: 10.1002/2016ms000846
|View full text |Cite
|
Sign up to set email alerts
|

On the role of the stratiform cloud scheme in the inter‐model spread of cloud feedback

Abstract: This study explores the role of the stratiform cloud scheme in the inter‐model spread of cloud feedback. Six diagnostic cloud schemes used in various CMIP (Coupled Model Intercomparison Experiment] climate models are implemented (at low and midlevels) into two testbed climate models, and the impacts on cloud feedback are investigated. Results suggest that the choice of stratiform cloud scheme may contribute up to roughly half of the intermodel spread of cloud radiative responses in stratocumulus (Sc) regions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 58 publications
(104 reference statements)
2
28
0
Order By: Relevance
“…Most GCMs do not account for vertically varying cloud sinks in their computation of cloud fraction; for example, the most common type of cloud-fraction parameterization used in the combined CMIP3/CMIP5 ensemble is based on a diagnostic function of relative humidity alone (Geoffroy et al, 2017;Tompkins, 2005). This highlights the importance of correctly parameterizing the sinks of cloud condensates in global climate models (GCMs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most GCMs do not account for vertically varying cloud sinks in their computation of cloud fraction; for example, the most common type of cloud-fraction parameterization used in the combined CMIP3/CMIP5 ensemble is based on a diagnostic function of relative humidity alone (Geoffroy et al, 2017;Tompkins, 2005). This highlights the importance of correctly parameterizing the sinks of cloud condensates in global climate models (GCMs).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of correctly parameterizing the sinks of cloud condensates in global climate models (GCMs). Most GCMs do not account for vertically varying cloud sinks in their computation of cloud fraction; for example, the most common type of cloud-fraction parameterization used in the combined CMIP3/CMIP5 ensemble is based on a diagnostic function of relative humidity alone (Geoffroy et al, 2017;Tompkins, 2005). Recent work by Wall and Hartmann (2018) has shown that one such RH-based scheme does not reproduce the observed anvil peak in the deeply convecting tropics of CAM5 (Neale et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the LWP is extremely high, which could conceivably mean that the clouds are already relatively saturated with respect to further changes in droplet numbers, in line with the findings of Painemal and Minnis (2012) mentioned above. Geoffroy et al (2017) investigated the role of different stratiform cloud schemes to the inter-model spread of cloud feedbacks, looking at 14 models -four of which were used in the present study. They found that NorESM1-M, which diagnoses stratiform clouds based on relative humidity and atmospheric stability, had an opposite cloud feedback from models (including HadGEM2-ES, CSIRO-Mk3L-1-2 and IPSL-CM5A-LR) that diagnoses such clouds based solely on relative humidity.…”
Section: Discussionmentioning
confidence: 99%
“…However, they should give a fair representation of geographical distribution, and numbers are comparable between models. To estimate the effective radiative forcing of increasing CDNC by 50 % in the different models, we use the method of Gregory et al (2004), whereby the topof-atmosphere (TOA) radiative flux imbalance is regressed against the globally averaged surface air temperature change compared to the RCP4.5 simulations. To estimate the effective radiative forcing of increasing CDNC by 50 % in the different models, we use the method of Gregory et al (2004), whereby the global mean top of atmosphere radiative flux imbalance is regressed against the globally averaged sur-face air temperature change compared to the RCP4.5 simulations.…”
Section: Postprocessing and Analysesmentioning
confidence: 99%